The concept of moderation among Islamic pious predecessors - Yabi S.; Ibrahim N.; Doll Kawaid A.I.S. (Kolej University Islam Sultan Azlan Shah, 2024)
Islam is religion of simplicity, moderation, just and perfect that leads its followers to the rightful path. Moderation is an important aspect in our daily life. Prophet Muhammad praise be upon him (PBUH) moderate lifestyle is a perfect exemplary. These exemplary has been adapted by previous Islamic scholars in their daily life thus they had emphasized the importance of understanding Al-Quran and Sunnah based on the understanding of previous pious predecessors. Some of the factors that had caused the digression are the diversion, misunderstanding and misinterpretation resulting to improper understanding of the concept on moderation. All these had caused misunderstanding and conflict of interests among us that had caused a disaster to the community. Results of the study found that the pious predecessors had drawn the concepts of moderations in five aspects of life. They are moderation in doing justice and goodness, doing pious deeds, in managing the economic and financial, in following the rightful path and finally moderation in leading our daily life following the exemplary of Prophet Muhammad PBUH.